2014
DOI: 10.1039/c4ra08847f
|View full text |Cite
|
Sign up to set email alerts
|

Red and near infrared persistent luminescence nano-probes for bioimaging and targeting applications

Abstract: Schematic representation of the different processes in persistent luminescence: charging (1), stimulation (2), discharging (3) (PET-persistent energy transfer, QT-quantum tunneling).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(87 citation statements)
references
References 154 publications
2
79
0
Order By: Relevance
“…[1][2][3][4] Chromium-doped gallates especially, have been studied intensively because of their near-infrared emission, situated in the first tissue transparency window (between 650 and 950 nm 5 ), and their long afterglow times. [6][7][8][9] Research on Cr-doped nanophosphors has shown that these materials have good chemical stability and low toxicity, necessary conditions for imaging applications.…”
mentioning
confidence: 99%
“…[1][2][3][4] Chromium-doped gallates especially, have been studied intensively because of their near-infrared emission, situated in the first tissue transparency window (between 650 and 950 nm 5 ), and their long afterglow times. [6][7][8][9] Research on Cr-doped nanophosphors has shown that these materials have good chemical stability and low toxicity, necessary conditions for imaging applications.…”
mentioning
confidence: 99%
“…The utilization of persistent luminescent nanophosphors as bioimaging contrast agents provides three important advantages: it allows to obtain images without external excitation, eliminating the autofluorescence, and improving the signalto-noise ratio; emission from persistent luminescence materials are in the range 650-1000 nm which is within the biological optical window, increasing the detection depth; and persistent luminescent nanophosphors may be re-activated after a long period of inactivity using incoherent light sources [52,54,55].…”
Section: Persistent Luminescence Nanophosphorsmentioning
confidence: 99%
“…The synthetic methods used for the synthesis of persistent luminescent nanophosphors include co-precipitation, sol-gel, and solvothermal techniques followed by high-temperature post-annealing. Hightemperature synthesis techniques such as solid-state reaction and combustion synthesis have also been applied [52].…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…For a deeper and more detailed description of these matters, some excellent reviews can be found in the recent literature [19,[29][30][31][32][33][34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%